Statistical Practices of Safety Monitoring: An Industry Survey. (May 2019) - Colopy, Michael W.; Gordon, Robert; Ahmad, Faiz; Wang, William W.; Duke, Susan P.; Ball, Greg
The Biopharmaceutical Section of the American Statistical Association (ASA) formed a Safety Monitoring Working Group to strengthen collaborations between biostatisticians and safety scientists. The task began by surveying current needs and practices regarding available statistical safety tools and methods, regulatory guidance, and processes needed to support their implementation. The goal is for biostatisticians to become fully engaged safety team members by having the necessary safety skill set including appropriate methodology, regulatory guidance and access to appropriate tools. In this publication, we will discuss our survey results that reveal current practices at 22 pharmaceutical companies and demonstrate how the survey instrument can be used to map an action plan for meeting the demand for improved quantitative safety monitoring.